(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This study explores the factors that influence the use of QRIS as a digital payment method in Pekanbaru City using the Unified Theory of Acceptance and Use of Technology 3 (UTAUT-3) approach. The sample of this study consisted of 100 respondents who were purposefully selected, including respondents of various ages, occupations, and frequencies of QRIS use in Pekanbaru City. Data were analysed using the SmartPLS application. The results show that habit (H) has a significant effect on Behavioral Intention (BI) and usage behaviour (UB). In addition, Hedonic motivation (HM), personal Innovativeness (PI), and Price Value (PV) are significant to BI, while PI also directly affects UB. In contrast, BI on UB, Effort expectancy (EE), Facilitating Conditions (FC), performance expectancy (PE), and Social influence (SI) do not show a significant effect. These findings indicate the importance of strengthening user habits, hedonic values, and personal innovation in developing QRIS features and marketing strategies to accelerate its adoption. The findings of this study indicate the need for QRIS service developers, policymakers, and business actors to focus on strengthening user habits, increasing hedonic motivation, price-based incentives, and encouraging personal innovation to accelerate the adoption of QRIS as a digital payment method while expanding understanding of the factors that influence the adoption of digital payment technology in the context of QRIS.